(untitled) (Conference Zone, 2022)
This article discusses the history of computer graphics, the possibilities of teaching software Articulate Storyline Adobe Captivate 5, CourseLab, iSpring, AutoPlay Media Studio, the creation of various electronic didactic materials using pedagogical software.